Analisis Isi Mengenai Kekerasan Seksual pada Film Like & Share - Safitri, Nur Aida; Nurlita, Ita (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2024)
Currently, films have educational capabilities, namely the use of films in the world of education, to be able to convey messages to the audience. One film that has a message about the issue of sexual violence in Indonesia is the film titled